Modified Rao diversity coefficient considering species dissimilarity with respect to biological characteristics at the class level - Manila, Phoebe Anne Salvador (2009)
In the measure of Izsak and Papp (2000), the distance of two species is equal to the number of internodes form the species level to the lowest level of the taxonomic tree where a common ancestor of both species exists. This is commonly used in construction a taxonomic dissimilarity matrix. However, this measure gives insufficient information about species differences. This study proposed a method of calculating the species distances by using Rao dissimilarity coefficient to obtain the differences between classes with respect to biological characteristics. It aimed to formulate a diversity index that Rao class DISCs were normalized, transformed into the interval (4,5), and integrated into the taxonomic dissimilarity matrix. Then, Rao diversity coefficient was reformulated by integrating the new dissimilarity matrix. Illustrations were presented which showed that the modified Rao DIVC provided a measure that showed more information about the differences between species, with respect to their characteristics. An application on ecological data was presented comparing nine communities of the EMBC. The modified and taxonomic-based Rao DIVCs of the communities were compared using Spearman rank correlation. Result showed they were highly correlated but there were still distinctions between the methods